2017
DOI: 10.1038/bcj.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib–lenalidomide–dexamethasone vs lenalidomide–dexamethasone in relapsed multiple myeloma by previous treatment

Abstract: Carfilzomib, a proteasome inhibitor, is approved as monotherapy and in combination with dexamethasone or lenalidomide–dexamethasone (Rd) for relapsed or refractory multiple myeloma. The approval of carfilzomib–lenalidomide–dexamethasone (KRd) was based on results from the randomized, phase 3 study ASPIRE (NCT01080391), which showed KRd significantly improved progression-free survival (PFS) vs Rd (median 26.3 vs 17.6 months; hazard ratio (HR)=0.690; P=0.0001). This subgroup analysis of ASPIRE evaluated KRd vs R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 14 publications
(17 reference statements)
5
48
1
1
Order By: Relevance
“…24 While cardiovascular events occurred more frequently in the elderly population compared with patients aged <70 years, KRd demonstrated a favorable benefit-risk profile in elderly patients. 25 The ENDEAVOR study of carfilzomib and dexamethasone (Kd) versus Vd demonstrated prolonged PFS with Kd in patients with RRMM who received one to three prior lines of therapy and were aged 65 to 74 years (median: 15.6 vs 9.5 months; HR, 0.528, 95% CI, 0.382-0.728) or ≥ 75 years (median: 18.7 vs 8.9 months; HR, 0.383, 95% CI, 0.227-0.647). 26 While hypertension was the most common grade Due to the nature of drug development, clinical trials and regulatory approvals usually proceed with patients with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…24 While cardiovascular events occurred more frequently in the elderly population compared with patients aged <70 years, KRd demonstrated a favorable benefit-risk profile in elderly patients. 25 The ENDEAVOR study of carfilzomib and dexamethasone (Kd) versus Vd demonstrated prolonged PFS with Kd in patients with RRMM who received one to three prior lines of therapy and were aged 65 to 74 years (median: 15.6 vs 9.5 months; HR, 0.528, 95% CI, 0.382-0.728) or ≥ 75 years (median: 18.7 vs 8.9 months; HR, 0.383, 95% CI, 0.227-0.647). 26 While hypertension was the most common grade Due to the nature of drug development, clinical trials and regulatory approvals usually proceed with patients with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who received Kd or Vd at first relapse, median PFS (Kd vs Vd) was not evaluable vs 12.1 months for patients who were bortezomib‐naïve and 18.7 months vs 8.7 months for patients who received prior bortezomib, suggesting that patients who respond to prior proteasome inhibitor therapy benefit from carfilzomib . Similarly, in the ASPIRE trial, the median PFS was 29.6 months for patients who received KRd at first relapse and 25.8 months for patients who received KRd at second or third relapse (risk of progression or death compared with Rd arm was reduced by 29% and 28%, respectively) . Also, in ASPIRE, patients benefitted from carfilzomib at first relapse regardless of prior exposure to bortezomib (median PFS [KRd vs Rd], 29.6 months vs 20.6 months for bortezomib‐naïve; 29.3 months vs 15.9 months for prior bortezomib) …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the efficacy of carfilzomib in subgroups of patients categorized by number of previous lines of therapy, and among subgroups of patients with or without prior exposure to a proteasome inhibitor. In both ASPIRE and ENDEAVOR, patients who received carfilzomib‐containing regimens had improved median PFS compared with control groups regardless of whether patients were previously exposed to proteasome inhibitors . Additionally, patients who received carfilzomib at first relapse had a significant and clinically relevant improvement in PFS compared with patients who received standard of care at first relapse in both ASPIRE and ENDEAVOR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy and safety of twice-weekly carfilzomib-based therapies were previously demonstrated in the phase 3 ASPIRE and ENDEAVOR trials [16][17][18][19] . Importantly, the treatment effect of carfilzomib was confirmed across several patient subgroups [20][21][22][23][24][25][26] . The favorable benefit-risk profile of twiceweekly carfilzomib-based therapies versus standards of care (SOCs) provided an opportunity to consider the value of more convenient once-weekly carfilzomib therapy for patients with RRMM.…”
Section: Introductionmentioning
confidence: 99%